The Secretive Liaison of Particulate Matter and SARS-CoV-2. A Hypothesis and Theory Investigation - Mescoli, Ada; Maffei, Giangabriele; Pillo, Gelsomina; Bortone, Giuseppe; Marchesi, Stefano; Morandi, Elena; Ranzi, Andrea; Rotondo, Francesca; Serra, Stefania; Vaccari, Monica; Zauli Sajani, Stefano; Mascolo, Maria Grazia; et al. (Frontiers in Genetics, 2020)
As the novel coronavirus disease sweeps across the world several speculations have been made on the role that atmospheric factors may have played on the different distribution of SARS-CoV-2 and on the epidemiological characteristics of COVID-19. Knowing the role that environmental factors play in influenza virus outbreaks, environmental pollution and, in particular, atmospheric airborne (PM) has been considered as a potential key factor in the spread and mortality of COVID-19. A possible role of the PM as the virus carrier has been also debated. The role of PM in exacerbating respiratory and cardiovascular disease has been well recognized. Accumulating evidence support the hypothesis that PM can trigger inflammatory response at molecular, cellular and organ levels. On this basis, we developed the hypothesis that PM my play a role as a booster of COVID-19 rather than as a carrier of SARS-CoV2. To support our hypothesis, we analyzed the molecular signatures detected in cells exposed to PM samples collected in one of the most affected areas by the COVID-19 outbreak, in Italy. T47D human breast adenocarcinoma cells were chosen to explore the global gene expression changes induced by the treatment with organic extracts of PM2.5. The analysis of the KEGG’s pathways showed modulation of several gene networks related to the leucocyte transendothelial migration, cytoskeleton and adhesion system. Three major biological process were identified, including coagulation, growth control and immune response. The analysis of the modulated genes gave evidence for the involvement of PM in the endothelial disease, coagulation disorders, diabetes and reproductive toxicity, supporting the hypothesis that PM, directly or through molecular interplaying, affects the same molecular targets as so far known for SARS-CoV, contributing to the cytokine storm and to the aggravation of the symptoms triggered by COVID-19. We provide evidence for a plausible cooperation of receptors and transmembrane proteins, targeted by PM and involved in COVID-19 and new insights into the molecular interplaying of chemicals and pathogens that could be of importance for sustaining public health policies and developing new therapeutic approaches